Corporate representations of the child worker: Swedish company websites offering sales opportunities to schoolchildren. Issue 4 (2nd October 2017) - Sjöberg, Johanna; Smith-MacGowan, Nigel
Abstract: The study explores how companies specialised in a schoolchild work force represent children's work and the working child on their official websites. The material is four websites from Swedish companies explicitly offering schoolchildren under 13 opportunities to sell products on commission in order to raise money for school trips. The analysis reveals there is an almost total visual absence of children performing work. Instead focus is placed on joy and on learning skills for the future. Caring adults are highly involved in the work that is described as safe and easy. Any possible negative connotations to exploited child labourers are avoided. These findings contribute to our understanding of how complex and contradictory the image of children is in prosperous societies where children do not have to work for survival, but yet do work.